Urate-lowering therapy and the risk of developing type 2 diabetes mellitus in patients with gout (results of a prospective study) - M. S. Eliseev; O. V. Zhelyabina (Современная ревматология, 2023)
Objective: to analyze the association between medications intake and the development of type 2 diabetes mellitus (T2DM) in patients with gout.   Material and methods. The study included 444 patients with gout without T2DM. The median follow-up time was 5.9 [2.9; 8.7] years. The primary end point was the diagnosis of T2DM. At baseline, therapy was initiated or adjusted according to current guidelines. Medication use was recorded: allopurinol, febuxostat, diuretics, glucocorticoids (GC), canakinumab, for which the odds ratio (OR) of developing T2DM was calculated.   Results and discussion. T2DM occurred in 108 (24.3 %) patients enrolled in the study. 405 patients completed the study. 311 (76.7 %) patients were taking urate-lowering drugs: 263 (90.7 %) allopurinol, 48 (9.3 %) febuxostat. The mean dose of allopurinol was 153.4 ± 28.4 mg/day, and that of febuxostat was 91.6 ± 12.1 mg/day. During treatment with febuxostat, the probability of developing T2DM was lower: OR 0.433 (95 % confidence interval, CI 0.188–0.996; p = 0.044). When diuretics were used OR was 2.212 (95 % CI 1.303–3.753; p = 0.003), GC – 1.566 (95 % CI 1.003–2.445; p = 0.048).   Conclusion. Febuxostat use is associated with a lower likelihood of developing T2DM.